Ceramic–polymer hybrid coatings for diverse applications - K R C, Soma Raju; R, Subasri; K, Srinivasa Rao (Frontiers in Coatings, Dyes and Interface Engineering, 2024)
Sol-gel process is a simple wet chemical method to generate nano-crystalline or nano-scaled amorphous ceramic, ceramic-polymer hybrid coatings. Pure ceramic and pure polymer coatings have certain limitations for use over a wide range of applications, due to the high temperature heat treatment requirement for the former and poor mechanical properties of the latter. Hence, ceramic-polymer hybrid coatings are the need of the hour for use in diverse applications on different substrates. Further, bioinspired multifunctional coatings that mimic complex geometrics of lotus leaf, pitcher plant etc. are being investigated for use in corrosion protection, biofilm inhibition, antifouling etc. Such complex geometries can be generated by a combination of physical and chemical modification of a surface. In case of chemical modification of a surface, instead of a pure ceramic or pure polymer coating, a ceramic-polymer hybrid coating would be the choice as it provides a rigid backbone by the ceramic (metal oxide network) moiety and a flexible structure by the polymeric moiety. This review will be discussing the sol-gel derived pure ceramic and ceramic-polymer hybrid coatings, their applications, challenges, research gaps as they have been evolving over the years and two nature-inspired phenomenon namely superhydrophobicity and self-healing, that have been widely researched for use in various applications.